A pp material and a preparation method thereof
Patent Information
- Application Number
- CN202511263414.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-09-05
AI Technical Summary
但此方法可能会破坏PP材料的基材结构,影响其整体性能,并且在环保方面也面临压力,因为化学试剂的使用和处理可能会带来环境污染问题
(1)本申请通过羟基庚酸与辛烯同时接枝,可稳定制备表面能高、接枝效果好的PP材料;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer materials technology, specifically to a PP material and its preparation method. Background Technology
[0002] Polypropylene (PP) is a semi-crystalline thermoplastic produced by the addition polymerization of propylene monomers. PP is one of the most common plastics in the world, widely used in various industries due to its good processability, chemical resistance, heat resistance, and relatively low cost. Currently, there are various methods for preparing PP materials, mainly including solution polymerization, slurry polymerization, bulk polymerization, gas-phase polymerization, and combined bulk-gas-phase processes. These processes each have their own characteristics to adapt to different production needs and product performance requirements. In practical applications, PP materials, with their inherent advantages, are used in the automotive industry to manufacture lightweight parts; in the household appliance industry, they are widely used due to their good electrical insulation properties; in the packaging industry, their chemical resistance and low cost make them an ideal choice for packaging materials; and they also play an important role in building materials and furniture. Despite the wide application of PP materials in various fields, their surface properties still have significant shortcomings. The low surface energy has become a key factor restricting their further expansion into new applications. From a molecular structure perspective, PP molecules consist of nonpolar hydrocarbon chains, lacking active groups such as hydroxyl and carboxyl groups, and exhibiting high surface smoothness. This directly results in a surface energy typically below 34 mN / m. However, in actual production, whether it's painting automotive parts, printing packaging materials, or coating appliance casings, most coatings and inks require a substrate surface energy higher than 38 mN / m to form a stable bond. This surface energy mismatch means that during surface treatment, PP coatings can only adhere through physical adsorption, making them prone to peeling and blistering. Furthermore, mold release agents are often used during injection molding of PP materials to facilitate demolding. These residual mold release agents form an oily layer on the surface, further reducing surface energy and posing greater challenges to subsequent surface processing.
[0003] To improve the surface energy of PP materials, various methods have been employed. For example, flame treatment uses instantaneous high temperatures to induce oxidation and other reactions on the PP surface, temporarily increasing its polarity and surface energy. However, this method has significant drawbacks: its effectiveness is unstable, the degree of surface energy increase is difficult to control precisely, and it's challenging to achieve uniform treatment for complex structures, easily leading to localized over- or under-treatment. Chemical etching is another approach, using specific chemical reagents to corrode the PP surface, creating a microscopic rough structure to increase coating adhesion. However, this method may damage the PP substrate structure, affecting its overall performance, and also faces environmental challenges due to the potential pollution from the use and handling of chemical reagents. Therefore, developing a new method for effectively preparing ultra-high surface energy PP materials has significant practical implications and application value. Summary of the Invention
[0004] The purpose of this application is to provide a PP material with high surface energy.
[0005] To achieve the above objectives, the technical solution adopted in this application is as follows: a PP material is provided, the raw materials for which include polypropylene, hydroxyheptanoic acid, octene and an initiator are used to graft the hydroxyheptanoic acid and the octene as monomers onto the polypropylene molecular chain through the initiator.
[0006] As a preferred embodiment, the mass ratio of the hydroxyheptanoic acid to the octene is (7:10) to (10:7).
[0007] As another preferred embodiment, the initiator is one or more of di-tert-butyl peroxide, dicumyl peroxide, and CPB01.
[0008] This application also provides a method for preparing PP material, comprising the following preparation steps: S1: dissolving polypropylene particles to obtain a PP solution; S2: adding hydroxyheptanoic acid and octene to the PP solution under an inert atmosphere, adding an initiator dropwise, and then heating the reaction for a period of time; S3: after the reaction is completed, PP grafting products precipitate, and after drying, the PP material is obtained.
[0009] As another preferred option, the mass ratio of the hydroxyheptanoic acid to the octene is (7:10) to (10:7).
[0010] As another preferred embodiment, the mass ratio of the hydroxyheptanoic acid to the octene is 1% to 10% based on the total mass of the PP solution, the hydroxyheptanoic acid, and the octene.
[0011] As another preferred embodiment, the initiator is one or more of di-tert-butyl peroxide, dicumyl peroxide, and CPB01.
[0012] As another preferred embodiment, the initiator has a dropping rate of 3~8 mL / min and a reaction temperature of 130~140 ℃ after the initiator is added.
[0013] As another preferred embodiment, step S3 specifically involves: after the reaction is completed, slowly pouring the reaction solution into an excess of pure water or anhydrous ethanol to allow the PP graft product to precipitate, and then drying the PP graft product at high temperature to obtain the PP material.
[0014] Further preferably, step S1 specifically involves: dissolving the polypropylene particles in a toluene solution or a xylene solution, and stirring in an oil bath at 130~140 ℃ until completely dissolved to obtain the PP solution.
[0015] Compared with the prior art, the beneficial effects of this application are as follows: (1) This application can stably prepare PP materials with high surface energy and good grafting effect by simultaneously grafting hydroxyheptanoic acid and octene; (2) By adding octene, this application can adjust the compatibility of the reaction system, reduce side reactions, provide a favorable environment for the grafting of hydroxyheptanoic acid, improve its grafting rate, and thus achieve a significant increase in surface energy. (3) The PP material preparation method of this application has a stable grafting rate, environmentally friendly raw materials, and some materials are biodegradable, making it suitable for a variety of high-end scenarios. Detailed Implementation
[0016] The present application will be further described below with reference to specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0017] The terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are intended to cover non-exclusive inclusion, for example, a process, method, system, product, or device that includes a series of steps or units is not necessarily limited to those steps or units that are explicitly listed, but may include other steps or units that are not explicitly listed or that are inherent to such process, method, product, or device.
[0018] This application provides a PP material, the raw materials of which include polypropylene, hydroxyheptanoic acid and octene. The modification idea is to graft hydroxyheptanoic acid and octene onto polypropylene to obtain a PP material with high surface energy.
[0019] In this application, hydroxyheptanoic acid and octene are used as monomers to participate in the grafting reaction of polypropylene. The hydroxyheptanoic acid molecule contains polar groups such as hydroxyl and carboxyl groups. After being grafted onto the PP molecular chain through solution free radical reaction, it can increase the polar sites on the surface of PP material, thereby significantly improving the surface energy of the material and improving the surface properties of PP such as printability, paintability, and adhesion.
[0020] Hydroxyheptanoic acid is derived from renewable biomass. When grafted onto the PP molecular chain, it can introduce easily biodegradable structural units, giving PP materials partial biodegradability, reducing microplastic pollution, and making them suitable for high-end applications such as medical devices and biodegradable packaging.
[0021] Octene, as the second monomer, is a nonpolar olefin. Direct grafting onto the PP molecular chain has limited effect on improving the surface energy of PP materials. However, through synergistic interaction with hydroxyheptanoic acid, it can promote the grafting reaction of hydroxyheptanoic acid onto the PP molecular chain, thereby increasing the grafting rate of hydroxyheptanoic acid and thus achieving the goal of improving surface energy.
[0022] The addition of octene may indirectly assist hydroxyheptanoic acid to be grafted more uniformly onto the PP molecular chain by adjusting the compatibility of the reaction system and reducing side reactions caused by excessively high local concentrations, thus ensuring the stability of the reaction.
[0023] Hydroxyheptanoic acid is a key functional monomer for improving surface energy, but when grafted alone, its grafting rate may be low due to steric hindrance or limited reactivity, making it difficult to fully exert its effect. Octene, as a nonpolar monomer, provides a more favorable reaction environment for the grafting of hydroxyheptanoic acid through its interaction with the PP molecular chain and hydroxyheptanoic acid, significantly improving its grafting rate. Ultimately, hydroxyheptanoic acid with a high grafting rate can introduce more polar groups on the PP surface. Combined with the optimization of reaction uniformity by octene, the surface energy of the material is higher than when hydroxyheptanoic acid is used alone, achieving the technical goal of "ultra-high surface energy".
[0024] This application also provides a method for preparing PP material, including the following steps: S1: Dissolve polypropylene granules to obtain a PP solution; S2: Under an inert atmosphere, hydroxyheptanoic acid and octene are added to a PP solution, and an initiator is added dropwise, followed by a reaction at high temperature for a period of time; S3: After the reaction is complete, the PP graft product is precipitated, dried, and then the PP material is obtained.
[0025] In some embodiments, polypropylene particles are dissolved in a toluene or xylene solution and stirred in a high-temperature oil bath until completely dissolved, forming a homogeneous PP solution. Polypropylene is a crystalline polymer material and is poorly soluble in organic solvents such as toluene at room temperature. The high-temperature oil bath provides stable and sufficient heat, raising the temperature of toluene and enhancing its solubility in PP. This promotes the gradual dispersion and eventual complete dissolution of the PP particles, forming a homogeneous PP solution. This homogeneous system forms the basis for subsequent grafting reactions, ensuring sufficient contact between monomers such as hydroxyheptanoic acid and octene and the PP molecular chains, creating conditions for the uniform conduction of the grafting reaction.
[0026] In some embodiments, the temperature of the high-temperature oil bath reaction is 130~140 ℃.
[0027] In some embodiments, hydroxyheptanoic acid and octene are added to the PP solution. The proportion of hydroxyheptanoic acid is 1-10% based on the total mass of the PP solution, hydroxyheptanoic acid and octene, with a more preferred amount of 2-5%; the proportion of octene is 1-10%, with a more preferred amount of 2-5%.
[0028] In some preferred embodiments, the ratio of the amount of hydroxyheptanoic acid added to the amount of octene added is (7:10) to (10:7), and in a more preferred embodiment, the ratio of the amount of hydroxyheptanoic acid added to the amount of octene added is 1:1.
[0029] The mass ratio of hydroxyheptanoic acid to octene has a crucial impact on the surface energy and grafting rate of PP materials. When the ratio is appropriate, they can better exert a synergistic effect. Octene can adjust the compatibility of the reaction system and reduce side reactions, providing a favorable environment for the grafting of hydroxyheptanoic acid, helping to improve the grafting rate of hydroxyheptanoic acid, and thus promoting the improvement of the surface energy of PP materials to meet application requirements. If the ratio is inappropriate, it may disrupt the synergistic balance, making it difficult to effectively improve the grafting rate, resulting in poor improvement in the surface energy of PP materials and failing to achieve the expected performance targets.
[0030] Octene plays an indispensable role. As the second monomer involved in the polypropylene grafting reaction, although octene itself is a nonpolar olefin and its direct grafting has limited effect on improving the surface energy of PP materials, it can form a key synergistic effect with hydroxyheptanoic acid. It can regulate the compatibility of the reaction system, reduce side reactions caused by excessively high local concentrations of hydroxyheptanoic acid, and create a more favorable reaction environment for the grafting of hydroxyheptanoic acid onto the polypropylene molecular chain, thereby significantly improving the grafting rate of hydroxyheptanoic acid. The improvement of the grafting rate of hydroxyheptanoic acid is the core prerequisite for introducing more polar groups onto the surface of PP materials and achieving effective improvement in surface energy, ultimately helping to prepare PP materials that meet performance requirements and ensuring the stability and efficiency of the entire grafting modification process.
[0031] In some embodiments, the initiator is a peroxide initiator and a benzoyl initiator, preferably one or a mixture of di-tert-butyl peroxide, dicumyl peroxide, CPB01, etc. Under high-temperature reaction conditions, the initiator decomposes to generate free radicals. These free radicals can attack the polypropylene molecular chains, forming active free radical sites, which then react with monomers such as hydroxyheptanoic acid and octene, driving the grafting of monomers onto the PP molecular chains. The initiator acts as the "starter" for the entire grafting modification reaction. The proper use of the initiator can enhance the uniformity of the reaction system, improve the overall reaction efficiency, and provide a guarantee for ultimately achieving an increase in the surface energy of the PP material.
[0032] In some preferred embodiments, the dropping rate of the initiator is 3-8 mL / min. By controlling the dropping rate of the initiator, it is possible to avoid overly vigorous or uneven reactions caused by excessively high local concentrations of the initiator, thereby reducing the probability of side reactions such as excessive degradation of PP molecular chains and monomer self-polymerization.
[0033] In some embodiments, nitrogen gas is continuously introduced throughout steps S2 and S3 to purge air from the apparatus. During the grafting reaction, oxygen may combine with free radicals in the reaction system, leading to free radical deactivation and inhibiting the grafting reaction. Furthermore, oxygen may trigger side reactions such as monomer oxidation, affecting the purity and performance of the grafted product. By continuously introducing nitrogen gas, oxygen in the reaction system can be replaced, providing an inert environment for the reaction, ensuring the smooth progress of the free radical reaction, and reducing the impact of side reactions on product quality.
[0034] In some embodiments, the reaction temperature after adding the initiator in step S2 is 130~140 °C.
[0035] In some embodiments, after the reaction in step S3 is completed, the reaction solution is slowly poured into an excess of pure water or anhydrous ethanol to wash away the small molecules that have not been completely reacted. The PP grafted product is precipitated as a flocculent precipitate. The precipitated PP grafted product is dried at high temperature, stretched into strips and granulated to obtain the PP material of this application.
[0036] The reaction system may contain residual small molecules such as hydroxyheptanoic acid, octene, and initiators that did not participate in the grafting reaction. These small molecules are soluble in excess pure water or anhydrous ethanol, while the PP grafted product, due to its large molecular weight and polarity mismatch with the solvent, cannot be dissolved. This process separates the product from the impurities, improving the purity of the final product.
[0037] The preparation method of the PP material in this application is environmentally friendly. The raw material is derived from renewable biomass, and the grafting process gives the PP some biodegradability, reducing microplastic pollution. In addition, the flexibility of the PP material is improved to a certain extent, avoiding the increase in brittleness caused by traditional grafting of maleic anhydride. The degradation products are non-toxic and suitable for high-end applications such as medical devices and biodegradable packaging.
[0038] Example 1 Prepare a PP material by the following steps, in parts by weight: S1: Dissolve 140 parts of polypropylene granules in 490 parts of xylene solution, and stir in a high-temperature oil bath at 130~140 ℃ to completely dissolve the polypropylene granules and form a PP solution. S2: Under nitrogen atmosphere, add 8 parts of hydroxyheptanoic acid and 8 parts of octene to the dissolved PP solution, add 5.6 parts of di-tert-butyl peroxide to the PP solution at a dropping rate of 3 mL / min, and react at 130~140 °C for a period of time; S3: After the reaction is complete, the reaction solution is slowly poured into anhydrous ethanol. The PP graft product precipitates out as a flocculent precipitate. The precipitate is filtered, washed and dried to obtain a PP material.
[0039] Example 2 The amount of hydroxyheptanoic acid added was adjusted to 10 parts by mass, and the amount of octene added was adjusted to 10 parts by mass. Other preparation steps were the same as those in Example 1.
[0040] Example 3 The amount of hydroxyheptanoic acid added was adjusted to 14 parts by mass, and the amount of octene added was adjusted to 14 parts by mass. Other preparation steps were the same as those in Example 1.
[0041] Example 4 The amount of hydroxyheptanoic acid added was adjusted to 18 parts by mass, and the amount of octene added was adjusted to 18 parts by mass. Other preparation steps were consistent with the preparation steps in Example 1.
[0042] Example 5 The amount of hydroxyheptanoic acid added was adjusted to 14 parts by mass, and the amount of octene added was adjusted to 18 parts by mass. Other preparation steps were the same as those in Example 1.
[0043] Example 6 The amount of hydroxyheptanoic acid added was adjusted to 18 parts by mass, and the amount of octene added was adjusted to 14 parts by mass. Other preparation steps were the same as those in Example 1.
[0044] Comparative Example 1 In step S2, only 10 parts by mass of hydroxyheptanoic acid are added to the dissolved PP. The other preparation steps are consistent with the preparation steps in Example 2.
[0045] Comparative Example 2 In step S2, only 14 parts by mass of hydroxyheptanoic acid are added to the dissolved PP. The other preparation steps are consistent with the preparation steps in Example 3.
[0046] Comparative Example 3 In step S2, only 18 parts by mass of hydroxyheptanoic acid are added to the dissolved PP. The other preparation steps are consistent with the preparation steps in Example 4.
[0047] Comparative Example 4 In step S2, only 10 parts by mass of octene are added to the dissolved PP, and the other preparation steps are consistent with the preparation steps in Example 2.
[0048] Comparative Example 5 In step S2, only 14 parts by mass of octene are added to the dissolved PP, and the other preparation steps are consistent with the preparation steps in Example 3.
[0049] Comparative Example 6 In step S2, only 18 parts by mass of octene are added to the dissolved PP, and the other preparation steps are consistent with the preparation steps in Example 4.
[0050] Comparative Example 7 In step S2, 14 parts by mass of hydroxyheptanoic acid and 14 parts by mass of styrene are added to the dissolved PP. The other preparation steps are consistent with the preparation steps in Example 3.
[0051] Performance testing 1. Surface Energy: According to ISO 15989, the surface energy of the test material is ≥40 dyne / cm using the contact angle measurement method.
[0052] 2. Titration method for testing grafting rate: Take about 1 g (m) of purified graft material into a four-necked flask, add 200 ml of xylene to the flask, fix the stirring, condensing, reflux and exhaust device, heat to 140℃, stir continuously for about 30 min-1 h, after the graft material is completely dissolved, start cooling, when the temperature drops to about 100 ℃, add 2 drops of distilled water to extract unreacted base, when the temperature drops to 80 ℃, add 2 drops of phenolphthalein, and add about 8 ml of KOH-ethanol standard solution with a burette until the system is deep red, back titrate with HCl-isopropanol standard solution until the system is just colorless, and record the result; Grafting rate G% = (v 空白 -v 样品 )*C HCl *M HPA / (m*n COOH ) The performance test results of each embodiment and each comparative example are recorded in Table 1 below.
[0053] Table 1 Performance test results of each embodiment and each comparative example
[0054] In Comparative Examples 1-3, the highest surface energy achieved by adding only hydroxyheptanoic acid was 38 dyne / cm, failing to reach the target of ≥40 dyne / cm; the highest grafting rate was only 0.7%, far lower than the lowest grafting rate of 1% in the examples. This indicates that using hydroxyheptanoic acid alone results in low grafting efficiency due to steric hindrance or limited reactivity, and cannot sufficiently improve the surface energy.
[0055] In Comparative Examples 4-6, the surface energy of octene alone was only 30 dyne / cm, and the grafting rate was only 0.4%. This verifies that octene itself is a nonpolar olefin, and its use alone not only fails to improve surface energy but may also affect the surface properties of the material due to poor grafting effect.
[0056] Examples 1 through 6 all simultaneously added hydroxyheptanoic acid and octene, achieving surface energies ≥44 dyne / cm and grafting rates ≥1%, with the highest surface energy reaching 50 dyne / cm and the highest grafting rate being 1.4%. The surface energies and grafting rates of Examples 1 through 6 are significantly higher than those of the comparative examples using either monomer alone. This demonstrates that octene can improve the grafting rate of hydroxyheptanoic acid by adjusting the compatibility of the reaction system and reducing side reactions, thereby significantly increasing the surface energy. The synergistic effect of the two monomers is the core factor in achieving the goal of increasing surface energy.
[0057] In Examples 1-3, hydroxyheptanoic acid and octene were added in equal proportions. As the total amount added increased from 16 parts to 28 parts, the surface energy increased from 45 dyne / cm to 50 dyne / cm, and the grafting rate increased from 1% to 1.4%, showing a clear positive correlation. However, when the total amount continued to increase to 36 parts, the surface energy decreased to 46 dyne / cm, and the grafting rate decreased to 1.2%, indicating a performance decline. This shows that there is an optimal range of total amounts when the two are added in equal proportions. Excessive addition may lead to excessively high local concentrations, triggering side reactions such as monomer self-polymerization and excessive degradation of PP molecular chains, which in turn reduces grafting efficiency and surface energy.
[0058] In Examples 5 and 6, hydroxyheptanoic acid and octene were added in non-equilibrium proportions, resulting in lower surface energy and grafting rates compared to Example 2. At similar total addition amounts, the synergistic effect is better when hydroxyheptanoic acid and octene are added in equal proportions, which is more conducive to improving grafting rate and surface energy; non-equilibrium addition may disrupt the synergistic balance between the two, leading to a decrease in performance.
[0059] The performance test results of Example 3 and Comparative Example 7 show that in the grafting system of hydroxyheptanoic acid and styrene, the surface energy and grafting rate of PP material are significantly lower than those when octene is used. This indicates that styrene, unlike octene, cannot provide a favorable environment for hydroxyheptanoic acid grafting by adjusting the compatibility of the reaction system and reducing side reactions.
[0060] In summary, the PP materials prepared by the method of this application all have a surface energy of ≥44 dyne / cm, which is far higher than the industry's minimum surface energy requirement of 38 dyne / cm for coatings and inks. Moreover, the grafting rate of each embodiment is ≥1%, which ensures the effective grafting of hydroxyheptanoic acid onto the PP molecular chain.
[0061] This application describes a method for the stable preparation of PP materials with high surface energy and good grafting effect by simultaneously grafting hydroxyheptanoic acid and octene. The preparation method is simple, feasible, and stable.
[0062] The basic principles, main features, and advantages of this application have been described above. Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely the principles of this application. Various changes and modifications can be made to this application without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claims. The scope of protection claimed by this application is defined by the appended claims and their equivalents.
Claims
1. A PP material, characterized in that, The raw materials for preparation include polypropylene, hydroxyheptanoic acid, octene and an initiator. The hydroxyheptanoic acid and octene are grafted onto the polypropylene molecular chain as monomers through the initiator. The mass ratio of hydroxyheptanoic acid to octene is (7:10) to (10:7).
2. The PP material as described in claim 1, characterized in that, The initiator is one or more of di-tert-butyl peroxide, dicumyl peroxide, and CPB01.
3. A method for preparing PP material, characterized in that, The preparation steps include the following: S1: Dissolve polypropylene granules to obtain a PP solution; S2: Hydroxyheptanoic acid and octene are added to the PP solution under an inert atmosphere. After adding an initiator, the temperature is raised and the reaction is carried out for a period of time. The mass ratio of hydroxyheptanoic acid to octene is (7:10) to (10:7). S3: After the reaction is complete, the PP graft product is precipitated and dried to obtain the PP material.
4. The preparation method according to claim 3, characterized in that, Based on the total mass of the PP solution, the hydroxyheptanoic acid, and the octene, the mass ratio of the hydroxyheptanoic acid is 1% to 10%, and the mass ratio of the octene is 1% to 10%.
5. The preparation method according to claim 3, characterized in that, The initiator is one or more of di-tert-butyl peroxide, dicumyl peroxide, and CPB01.
6. The preparation method according to claim 3, characterized in that, The initiator has a dropping rate of 3-8 mL / min, and the reaction temperature after adding the initiator is 130-140 °C.
7. The preparation method according to claim 3, characterized in that, The S3 step specifically involves: after the reaction is completed, slowly pouring the reaction solution into an excess of pure water or anhydrous ethanol to allow the PP graft product to precipitate, and then drying the PP graft product at high temperature to obtain the PP material.
8. The preparation method according to claim 3, characterized in that, The S1 step specifically involves dissolving the polypropylene particles in a toluene or xylene solution and stirring in an oil bath at 130-140 °C until completely dissolved to obtain the PP solution.
Citation Information
Patent Citations
High-grating-rate and low-odor polypropylene resin composition and preparation method thereof
CN103755878A
Polar polypropylene graft and preparation method thereof
CN108192027A
